Differentiating between Acidic and Basic Surface Hydroxyls on Metal Oxides by Fluoride Substitution: A Case Study on Blue TiO2 from Laser Defect Engineering. Issue 12 (14th February 2023) - Lau, Kinran; Niemann, Felix; Abdiaziz, Kaltum; Heidelmann, Markus; Yang, Yuke; Tong, Yujin; Fechtelkord, Michael; Schmidt, Torsten C.; Schnegg, Alexander; Campen, R. Kramer; Peng, Baoxiang; Muhler, Martin; et al.
Abstract: Both oxygen vacancies and surface hydroxyls play a crucial role in catalysis. Yet, their relationship is not often explored. Herein, we prepare two series of TiO2 (rutile and P25) with increasing oxygen deficiency and Ti 3+ concentration by pulsed laser defect engineering in liquid (PUDEL), and selectively quantify the acidic and basic surface OH by fluoride substitution. As indicated by EPR spectroscopy, the laser‐generated Ti 3+ exist near the surface of rutile, but appear to be deeper in the bulk for P25. Fluoride substitution shows that extra acidic bridging OH are selectively created on rutile, while the surface OH density remains constant for P25. These observations suggest near‐surface Ti 3+ are highly related to surface bridging OH, presumably the former increasing the electron density of the bridging oxygen to form more of the latter. We anticipate that fluoride substitution will enable better characterization of surface OH and its correlation with defects in metal oxides. Abstract : Probing surface OH with F − ions: Surface OH of TiO2 were substituted by F − ions, which were then quantified by XPS and ion chromatography. The acidic (bridging) and basic (terminal) surface OH can be distinguished at different pH. Using this fluoride substitution, it was demonstrated that laser defect engineering selectively created more acidic OH but not basic OH on TiO2 .